STRATEGI KOMUNIKASI PT INDOLAKTO DALAM MENINGKATAN PENJUALAN PRODUK INDOESKRIM - Demus, Nico; Suryawati, I Gusti Agung Alit; Pradipta, Ade Devia (E-Jurnal Medium, 2023)
Creative strategy is a planning carried out to achieve a specific goal to be achieved in an advertising. The problems want to be appointed is the thing that concerned with creative strategy Indoeskrim Nusantara